2019
DOI: 10.5650/jos.ess18220
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Selective Bactericidal Activity of Fatty Acids against <i>Staphylococcus aureus</i> with Minimum Inhibitory Concentration and Minimum Bactericidal Concentration

Abstract: INTRODUCTION Bacteria live on human skin surface and play crucial roles in various skin conditions 1. The microbiota on healthy skin surfaces contains many kinds of bacteria, such as Corynebacterium, Staphylococcus, and Propionibacteriaceae 2 4. Staphylococcal bacteria, including Staphylococcus aureus S. aureus and Staphylococcus epidermidis S. epidermidis are present in the nasal cavity or sebaceous glands. S. aureus causes inflammation of atopic dry skin as well as skin roughness and food poisoning 5, 6. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
(20 reference statements)
3
17
0
Order By: Relevance
“…In the case of myristic acid/palmitoleic acid mixed system, the turbidity increased under all mixed conditions: The antibacterial behavior was not observed against S. epidermidis. Palmitoleic acid also does not exhibit antibacterial activity against S. epidermidis as a single component as well as myristic acid 10 . This result suggests that the selective antibacterial activity against S. aureus is maintained even when the two components, which do not exhibit antibacterial activity against S. epidermidis, are mixed.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the case of myristic acid/palmitoleic acid mixed system, the turbidity increased under all mixed conditions: The antibacterial behavior was not observed against S. epidermidis. Palmitoleic acid also does not exhibit antibacterial activity against S. epidermidis as a single component as well as myristic acid 10 . This result suggests that the selective antibacterial activity against S. aureus is maintained even when the two components, which do not exhibit antibacterial activity against S. epidermidis, are mixed.…”
Section: Discussionmentioning
confidence: 92%
“…In the checkerboard method, a combined effect was determined based on the FIC index, which was calculated from the MIC of a mixture containing two types of ingredients. We have reported the MICs of myristic acid and three additives in a single component against S. aureus and S. epidermidis in previously Table 1 10,17 .…”
Section: Evaluation Of the Combined Effect Of Antibacterial Components Based On Checkerboard Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that the incorporation of a fatty acid into the acorane-type sesquiterpenoid derivative likely significantly increases the antimicrobial activity. The addition of a fatty acid could improve the penetration into the cell membrane, which may cause the antimicrobial activity [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…From then, many other studies have proven the bactericidal or bacteriostatic effect of several saturated and unsaturated fatty acids on Gram-positive and Gram-negative bacteria [20,30]. Nowadays, partially driven by the emergence of multidrug-resistant strains, the research on fatty acids and monoglycerides as potential antibacterial agents has gained new attention [30,31,32,33,34,35,36].…”
Section: Resultsmentioning
confidence: 99%